The Impact of the Decline in Oil Prices in Latin America - Minor, Rebeca Rodríguez (Journal of Social Economics Research, 2015)
International oil prices have been falling irreversibly. This is due to a complex structural phenomenon which is analyzed in the introductory part of this article; we then move on to the study of some of the nations that have gambled a significant part of their internal growth on petroleum production. As a result, they have seen the imperative need to restructure their strategies in order to ensure a consolidated revenue base. The problem is primarily reflected in those economies that have not known how to diversify their productive sectors and international markets, or they have not invested enough in the basic infrastructure, cutting-edge technology, and the research and development required to reduce their vulnerability and economic dependence on the trade of certain raw materials in the global economic system. Latin America demonstrates various cases of this kind, such as Venezuela and Mexico (traditionally oil countries), or Brazil and Argentina (recently venturing into the oil market). The objective of this article is to discuss the main challenges faced by each of these countries, to identify their similarities and differences, and finally, to propose strategies that could be implemented for the sustainable development of their economies. This is a descriptive, correlational, and explanatory investigation with a purely qualitative focus. Analysis of each case is carried out purely in a current timeframe. The information used for the study is based on the most recent international reports and global circumstances of the countries in question. This investigation took place in the year 2015 over a five-month period.